2006
DOI: 10.1091/mbc.e06-04-0320
|View full text |Cite
|
Sign up to set email alerts
|

Wnt5a Signaling Induces Proliferation and Survival of Endothelial Cells In Vitro and Expression of MMP-1 and Tie-2

Abstract: Wnts are lipid-modified secreted glycoproteins that regulate diverse biological processes. We report that Wnt5a, which functions in noncanonical Wnt signaling, has activity on endothelial cells. Wnt5a is endogenously expressed in human primary endothelial cells and is expressed in murine vasculature at several sites in mouse embryos and tissues. Expression of exogenous Wnt5a in human endothelial cells promoted angiogenesis. Wnt5a induced noncanonical Wnt signaling in endothelial cells, as measured by Dishevell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
163
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(178 citation statements)
references
References 36 publications
13
163
2
Order By: Relevance
“…To further investigate whether CD146 can activate non-canonical Wnt signalling JNK alone, the expression levels of Wnt5a and several Wnt receptors were examined by reverse transcriptase-PCR in HEK293T and HUVECs. Our results show that Wnt5a and Wnt receptors were expressed in those cells as reported [21][22][23] . Subsequently, specific siRNAs were employed to knock down the different Wnt receptors in HEK293T cells ( Supplementary Fig.…”
supporting
confidence: 86%
“…To further investigate whether CD146 can activate non-canonical Wnt signalling JNK alone, the expression levels of Wnt5a and several Wnt receptors were examined by reverse transcriptase-PCR in HEK293T and HUVECs. Our results show that Wnt5a and Wnt receptors were expressed in those cells as reported [21][22][23] . Subsequently, specific siRNAs were employed to knock down the different Wnt receptors in HEK293T cells ( Supplementary Fig.…”
supporting
confidence: 86%
“…It was also shown previously that Wnt5a induces the expression of MMP-1 in endothelial cells although the mechanism was not known (Masckauchan et al, 2006). This study found that Wnt5a induces the phosphorylation of PKD/ PKCm, which is a direct target of novel PKCs (PKCd, PKCe, PKCZ and PKCy), and activates JNK.…”
Section: Mechanism By Which Wnt5a Promotes Aggressiveness Of Pcasupporting
confidence: 53%
“…The siRNA sequences used were: Ror2 siRNA #1, 5 0 -GCAA T G T GC T AG T G T ACGA TT-3 0 ; control siRNA #1, 5 0 -G T ACCGCACG T CA TT CG T A T C-3 0 (RNAi Co., Ltd, Tokyo, Japan); Ror2 siRNA #2, 5 0 -TAAAGGGTCGTTCGGATCCAGAACC-3 0 ; control siRNA #2, Medium GC Duplex 2 (Invitrogen); MMP-13 siRNA 5 0 -GATAACACCTTAGATGTCATT-3 0 (Sigma, St Louis, MO, USA). The Wnt5a siRNA was as described by Masckauchan et al (2006). An anti-Ror2 antibody was prepared as previously described by Kani et al (2004).…”
Section: Plasmids and Sirnasmentioning
confidence: 99%
“…It has been shown that Ror2 mediates Wnt5a signaling by activating the Wnt/JNK pathway and inhibiting the b-catenin-TCF pathway (Oishi et al, 2003;Mikels and Nusse, 2006). Studies using cultured mammalian cells show that Wnt5a promotes cell migration (Weeraratna et al, 2002;Kodama et al, 2004;Masckauchan et al, 2006), and that Ror2 mediates Wnt5a-induced cell migration through its association with the actin-binding protein, filamin A (Nishita et al, 2006). In addition, it has recently been reported that Wnt5a regulates cell polarity in cooperation with Par/Atypical protein kinase C pathway (Schlessinger et al, 2007), and that Ror2 mediates Wnt5a-induced polarized cell migration by activating JNK through its association with filamin A (Nomachi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%